2019
DOI: 10.1177/1753193419849767
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of scaphoid fractures in Sweden: a nationwide registry study

Abstract: The epidemiology of scaphoid fractures has been described in limited populations, and incidence reports have been inconsistent. We investigated the nationwide incidence of scaphoid fractures by evaluating data on 34,377 patients in the Swedish National Patient Register for the years 2006–2015 regarding diagnosis, age, sex and treatment. The data were validated in 300 random patients, and incidence rates were adjusted accordingly. Forty-one per cent of the initially diagnosed fractures were false positives. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 16 publications
3
15
0
3
Order By: Relevance
“…However, it has previously been reported that females have a young as well as old age peak incidence [19,27]. In a recent register study, the scaphoid fracture incidence was approximately 15/100 000 for people above 70 years of age [20].…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…However, it has previously been reported that females have a young as well as old age peak incidence [19,27]. In a recent register study, the scaphoid fracture incidence was approximately 15/100 000 for people above 70 years of age [20].…”
Section: Discussionmentioning
confidence: 96%
“…At a national register encompassing 34,377 patients diagnosed as scaphoid fractures, the authors went through the medical charts and radiographic examinations of 300 randomly selected patients. They found that as many as 41 % of patients who initially were registered as having a scaphoid fracture in fact did not have a fracture [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations